2020
DOI: 10.1016/j.isci.2020.101563
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic and Cell-Specific Transcriptomes Unravel a Dynamic Neuropil Remodeling in Leptin-Induced and Typical Pubertal Transition in Female Mice

Abstract: Summary Epidemiological and genome-wide association studies (GWAS) have shown high correlation between childhood obesity and advance in puberty. Early age at menarche is associated with a series of morbidities, including breast cancer, cardiovascular diseases, type 2 diabetes, and obesity. The adipocyte hormone leptin signals the amount of fat stores to the neuroendocrine reproductive axis via direct actions in the brain. Using mouse genetics, we and others have identified the hypothalamic ventral p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 103 publications
(175 reference statements)
1
19
0
Order By: Relevance
“…For LepRb hypothalamic neurons, we pooled 3 mice per biological replicate and used 4 biological replicates (n=12 mice/experimental group). We found that using mice homozygous for both LepRb cre/cre and Rosa eGFP-L10a/ eGFP-L10a increases efficiency of the method ( Allison et al., 2018 ; Allison et al., 2015 ; Garcia-Galiano et al., 2017 ; Han et al., 2020 ). Make sure to screen for germline recombination in your mouse model to avoid harvesting the wrong cells and that Cre is expressed in the correct or expected cells by analysis of eGFP expression.…”
Section: Before You Beginmentioning
confidence: 93%
See 4 more Smart Citations
“…For LepRb hypothalamic neurons, we pooled 3 mice per biological replicate and used 4 biological replicates (n=12 mice/experimental group). We found that using mice homozygous for both LepRb cre/cre and Rosa eGFP-L10a/ eGFP-L10a increases efficiency of the method ( Allison et al., 2018 ; Allison et al., 2015 ; Garcia-Galiano et al., 2017 ; Han et al., 2020 ). Make sure to screen for germline recombination in your mouse model to avoid harvesting the wrong cells and that Cre is expressed in the correct or expected cells by analysis of eGFP expression.…”
Section: Before You Beginmentioning
confidence: 93%
“… Reverse Transcribe 3–5 μL RNA of both enriched RNAs and depleted RNAs with the Reverse Transcriptase of your choice. We used Superscript II (Invitrogen) and the reaction was primed with both oligo dT and random hexamers ( Burger et al., 2018 ; Burger et al., 2020b ; Han et al., 2020 ; Ruka et al., 2013 ). We also recommend creating a standard curve.…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
See 3 more Smart Citations